Analysis of Energy Conservation Behavior at the Kuwaiti Academic Buildings - Alomari, Majdi M.; El-Kanj, Hania; Topal, Ayse (International Journal of Energy Economics and Policy, 2020)
Understanding user’s behavior in buildings is crucial since user behavior significantly contributes to the overall building’s energy consumption. Therefore, this study aims to identify a user’s pro-environmental behavior, in particular, the energy conservation behavior (ECB) of university users in Kuwait. For this reason, this study creates a model whereby two variables, namely, environmental knowledge and awareness of consequences, are introduced and incorporated into the existing theory of planned behavior (TPB). The research data is acquired through questionnaires in keeping with Kuwait’s social norms and culture. The extended TPB model is tested using numerical analysis problems in partial least square structural equation modeling (PLS-SEM) to investigate the following variables: energy conservation behavior, intention, subjective norm, attitude, perceived behavioral control, environmental knowledge, and awareness. Results show the indirect effects of the two above mentioned variables on conservation behavior. The results also reveal that societal pressure and cultures significantly affect the users’ intention to engage in energy conservation behavior. The outcomes of this research suggest that there is a need to encourage energy conservation behavior changes in Kuwaiti academics’ buildings by supporting the antecedents, as well as eliminating barriers to pro-environmental actions. Keywords: Energy Conservation, Environmental Behavior, Higher Educational Institutes, Partial Least Square Structural Equation Modelling, Theory of Planned Behavior JEL Classifications: Q49, P36, I230, Z130 DOI: https://doi.org/10.32479/ijeep.10407